Identifikasi Gaya Belajar Peserta Didik dan Implikasinya terhadap Pembelajaran PAI di Kelas XI SMA Negeri 1 Tanjung Mutiara - Humairah, Siti; Wirdati, Wirdati (Lembaga Yasin AlSys, 2025)
Learning styles play a crucial role in influencing students' ability to comprehend, analyze, and solve learning-related problems. A mismatch between teaching approaches and students' learning styles often stemming from educators’ limited understanding in identifying learning preferences can hinder the effectiveness of instruction. This study aims to identify students’ dominant learning styles and analyze their implications for Islamic Religious Education (Pendidikan Agama Islam, PAI), which includes the components of Al-Qur’an Hadis, Fikih, Akidah, Akhlak, and Sejarah Kebudayaan Islam (SKI). The study employed a descriptive quantitative method involving 76 students as the sample. Data were collected using a validated and reliable learning style questionnaire and analyzed through descriptive statistics. The findings reveal that the visual learning style is the most dominant (36.3%), followed by auditory (33.3%) and kinesthetic (30.4%). These results offer valuable insights for developing PAI teaching strategies that are responsive to students’ learning styles. The findings underscore the importance of differentiated instructional approaches across all PAI components to foster a more effective, inclusive, and meaningful learning experience.